Abnormal twins: dog and cat - Pourlis, A; Tsingotjidou, A (Journal of the Hellenic Veterinary Medical Society, 2024)
A survey of congenital malformations in dog and cat relating to their abnormal embryonic twinning was carried out. According to the degree, sites and angle of fusion, they have various external variation and are classified as free asymmetric, conjoined symmetric or asymmetric twins and unequal conjoined twins (heteropagus or parasitic twins). This manuscript aims to describe and summarize these defects. Among the recorded duplications in dog, a number of common defects relates to cephalothoracopagus phenotype whereas some cases of caudal duplication or parasitic twins have been surveyed. Among the recorded publications in cat, a number of craniofacial duplications have been encountered, whereas, some cases of thoracopagus phenotype have also been described. The pathogenetic mechanisms of this condition, reported in veterinary practice, are discussed. The importance in clinical practice lies in the fact that abnormal embryonic twinning is commonly associated with dystocia. Treatment of the diseased animals is also of veterinary practice consideration. The manuscript finally introduces a framework of an essential national registry for the malformed companion animals.